Pelatihan Model Pentahelix dalam Penguatan Ekosistem Kewirausahaan Kaum Sarungan - suroto, suroto; Winatha, I Komang; Rizal, Yon; Rahmawati, Fanni; Wijoyo, Hadi; Turnip, Samuel; Salshabella, Dhea Clara (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This devotion program aims to enhance the entrepreneurial capacity of kaum sarungan through the implementation of the Pentahelix Model, involving government, academia, business actors, religious communities, and media. The program was carried out through counseling sessions, training, workshops, and mentoring focused on strengthening basic entrepreneurial knowledge, developing local wisdom–based products, and expanding market networks. Evaluation was conducted using pre-test and post-test assessments as part of the monitoring and evaluation process. The results show a significant improvement in participants’ abilities, with an increase in average scores from 48 to 80. The N-Gain value of 60.43% indicates that the program is moderately effective in improving entrepreneurial literacy and skills. Beyond knowledge enhancement, the program successfully fostered multi-stakeholder collaboration and strengthened the pesantren-based entrepreneurial ecosystem. The integration of local wisdom also contributed to strengthening product identity developed by participants. Overall, this community service program provides a positive impact on the economic empowerment of kaum sarungan and demonstrates that the Pentahelix Model is effective in community-based capacity building.